Prognosis of idiopathic cardiomegaly in Jamaica with reference to the coronary arteries and other factors. (1971) - Stuart, K. L.; Bras, G.
Abstract : Clinical and epidemiological features of idiopathic cardiomegaly in Jamaica are reviewed, and the high community prevalence of the disorder is shown. The frequent occurrence of sudden or unexpected death in patients whose earlier electrocardiograms had shown repeated ventricular ectopic beats has been noted. Common electrocardiographic findings included a high rate of abnormalities usually regarded as indicative of coronary artery disease: cardiac arrhythmias, particularly multiple ventricular extrasystoles; and high voltage complexes characteristic of left ventricular hypertrophy. The differences and similarities between idiopathic cardiomegaly and coronary heart disease are shown. A possible role for intramuscular lignocaine in the control of the chronic ventricular ectopic rhythms is demonstrated. There is a statistically significant association between idiopathic cardiomegaly and positive serological tests for treponemal infection. The hearts are invariably hypertrophied at necropsy. In some hearts the smaller intramuscular coronary arteries show occlusive changes. Their possible nature and significance are discussed.